2016
DOI: 10.1097/j.pain.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pain outcomes after traumatic musculoskeletal injury

Abstract: Traumatic musculoskeletal injury results in a high incidence of chronic pain; however, there is little evidence about the nature, quality, and severity of the pain. This study uses a prospective, observational, longitudinal design to (1) examine neuropathic pain symptoms, pain severity, pain interference, and pain management at hospital admission and 4 months after traumatic musculoskeletal injury (n = 205), and (2) to identify predictors of group membership for patients with differing moderate-to-severe putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 41 publications
2
38
0
1
Order By: Relevance
“…Additionally, more information about the context in which the acute pain occurred (e.g., initial pain ratings, injury severity) and assessment of factors relevant to injury-related pain (e.g., post-traumatic stress) may be valuable. For example, research in adults hospitalized after traumatic injuries has identified post-traumatic stress and injury variables as relevant to pain outcomes [31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, more information about the context in which the acute pain occurred (e.g., initial pain ratings, injury severity) and assessment of factors relevant to injury-related pain (e.g., post-traumatic stress) may be valuable. For example, research in adults hospitalized after traumatic injuries has identified post-traumatic stress and injury variables as relevant to pain outcomes [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Additional data suggests post-injury anxiety, depression, posttraumatic stress symptoms, and pain catastrophizing predict pain persistence after acute injury [2; 31]. The developmental and interpersonal factors unique to childhood may limit the generalizability of these adult findings, making it critical to conduct similar prospective studies of youth with new-onset MSK pain.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, up to 24% of injured trauma patients report a new‐onset psychiatric disorder at 12 months postinjury, and an estimated 10%–40% develop clinically significant symptoms characteristic of posttraumatic stress disorder (PTSD), including intrusive experiences (e.g., nightmares, flashbacks, or triggers), avoidance of trauma‐related stimuli, negative changes in beliefs and feelings, and increased physiological arousal and reactivity . These psychological reactions are associated with chronic posttraumatic pain, even more so than injury severity or characteristics . Additionally, activation of support networks immediately after a traumatic event enhances adjustment to pain, and poor social support predicts adverse psychological outcomes …”
mentioning
confidence: 99%
“…Taken together, psychiatric symptoms may be involved in the transition from episodic to chronic migraine and more generally from acute to chronic pain . Yet, it remains unknown whether the relationship between acute psychological symptoms and headache‐related disability emerges soon after traumatic physical injury, and whether these psychological symptoms may be involved in the transition to chronic disability.…”
Section: Acute Headache–psychiatric Comorbiditymentioning
confidence: 99%